Assessment of plant growth promoting rhizobacteria for plant growth enhancement and biocontrol activity against Fusarium pseudograminearum on wheat - Labuschagne, Nico (University of Pretoria, 2020)
Dissertation (MSc (Agric))--University of Pretoria, 2019.